An analytical approach to study performance parameters of 1-3 piezoelectric composite - Singh S.K.; Panda S.K. (My University, 2025)
Exact solutions based on modified model of strength of materials has been derived to evaluate the performance parameters of 1-3 piezoelectric composites used for sensors and actuators applications. The effective thermo-electro-elastic coefficients have been derived as a function of fiber volume fractions based on developed analytical model and M ori-Tanaka approximations. The parameters such as hydrostatic charge coefficients, electromechanical coupling factor, hydrophone figure of merit, the acoustic impedance, stiffened longitudinal velocity and electro-elastic coupling coefficients are evaluated to illustrate the performance of 1-3 piezocomposites. The results show that the values of effective performance parameters lie between variational bounds of present analytical model and M ori-Tanaka approximations. © 2021 Author(s).